A Matrix Lie Superalgebra and Its Applications - Jingwei Han; Jing Yu; Jingsong He (Advances in Mathematical Physics, 2013)
A matrix Lie superalgebra is established. As its applications, multicomponent super Ablowitz-Kaup-Newell-Segur (AKNS) equations and multicomponent super Dirac equations are constructed. By making use of supertrace identity, their super-Hamiltonian structures are presented, respectively.